The Impact of Tourist Destination Image and Satisfaction on Tourist Loyalty - Bursan, Rinaldi (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study examines the impact of tourist destination image and satisfaction on tourist loyalty on Pahawang Island, located in Pesawaran Regency, Lampung. With regional autonomy emphasizing the importance of tourism for economic development, this research explores how these factors influence loyalty among tourists. Utilizing a non-probability sampling method with a judgment sampling technique, data were collected from 100 respondents and analyzed using multiple linear regression.The findings reveal that tourist satisfaction is the dominant factor in shaping loyalty, significantly more influential than the image of the tourist destination. Specifically, satisfaction accounted for the largest variance in loyalty among tourists visiting Pahawang Island. The study underscores the need for the local government to focus on preserving the natural environment and marine ecosystem of the island to ensure sustained tourist satisfaction and loyalty. This includes maintaining fish populations crucial for fishing activities, enhancing beach security, and providing adequate safety facilities and infrastructure such as boat rentals and fishing equipment. The research highlights the critical role of satisfaction in tourist loyalty and suggests that strategic efforts to enhance visitor experiences can lead to increased repeat visits and sustained economic benefits for the region.